Pengaruh Ukuran Perusahaan, Profitabilitas, dan Likuiditas Terhadap Pertumbuhan Laba - Monica Viola Yuliana; Mira Kartika Dewi Djunaedi (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2023)
This study aims to analyze the effect of firm size, profitability, and liquidity on profit growth. The research method used is a quantitative method which aims to analyze data to determine the relationship between variables in this study. This study used a purposive sampling method and obtained 23 companies from a total of 25 food and beverage sub-sector companies listed on the Indonesia Stock Exchange in the 2017-2021 period. The data analysis method used is the STATA version 17 application program. The results of the study show that partially the firm size is not significant and positive on profit growth, profitability is not significant and positive on profit growth, and liquidity is not significant and negative on profit growth.